Hemodynamic and metabolic parameters during prolonged cardiac arrest and reperfusion by extracorporeal circulation - Mlček, M; Ošťádal, P; Bělohlávek, J; Havránek, Š; Hrachovina, M; Huptych, M; Hála, P; Hrachovina, V; Neužil, P; Kittnar, O (Physiological research, 2012)
Extracorporeal membranous oxygenation (ECMO) is increasingly used in the management of refractory cardiac arrest. Our aim was to investigate early effects of ECMO after prolonged cardiac arrest. In fully anesthetized swine (48 kg, N=18) ventricular fibrillation (VF) was induced and untreated period (20 min) of cardiac arrest commenced, followed by 60 min extracorporeal reperfusion (ECMO flow 100 ml/kg.min). Hemodynamics, arterial blood gasses, plasma potassium, tissue oximetry (StO(2)) and cardiac (EGM) and cerebral (BIS) electrophysiological parameters were continuously recorded and analyzed. Within 3 minutes of VF hemodynamic and oximetry parameters fall abruptly while metabolic parameters destabilize gradually over 20 minutes peaking at pH 7.04 ± 0.05, pCO(2) 89 ± 14 mmHg, K(+) 8.5 ± 1.6 mmol/l. During reperfusion most parameters restore rapidly: within 3-5 minutes mean arterial pressure reaches >40 mmHg, StO(2)>50 %, paO(2)>100 mmHg, pCO(2)<50 mmHg, K(+)<5 mmol/l. EGMs mean amplitude peaks at 4.5 ± 2.4 min. Cerebral activity (BIS>60) reappeared in 5 animals after 87 ± 21 min. In 12/18 animals return of spontaneous circulation was achieved. In conclusions, ECMO provides rapid restitution of internal milieu even after prolonged arrest. However, despite normalization of global parameters full recovery was not guaranteed since cardiac and cerebral electrical activities were sufficiently restored only in some animals. More sensitive and organ specific indicators need to be identified in order to estimate adequacy of cardiac support devices.
Keywords: Animals; kardiopulmonální resuscitace; Hemodynamics; Cardiopulmonary Resuscitation; hemodynamika; mimotělní oběh; Heart Arrest; prasata; fibrilace komor; analýza krevních plynů; Myocardial Reperfusion; modely nemocí na zvířatech; Swine; srdeční zástava; Ventricular Fibrillation; Disease Models, Animal; Blood Gas Analysis; Arterial Pressure; zvířata; arteriální tlak; Extracorporeal Circulation; reperfuze myokardu